PENGARUH MEDIA PEMBELAJARAN BERBASIS CANVA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VI PADA PEMBELAJARAN IPAS DI UPTD SD NEGERI 122349 PEMATANGSIANTAR - Mindoria Munthe; Aprido Bernando Simamora; Eva Pasaribu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the effect of Canva-based learning media on elementary students’ critical thinking skills. The purpose of this research is to determine whether the use of Canva can improve the critical thinking skills of sixth-grade students in science (IPAS) learning on the solar system topic at UPTD SD Negeri 122349 Pematangsiantar. This study employed a quantitative approach using a pre-experimental One Group Pretest-Posttest Design with a sample of 25 students. Data were collected through pretest and posttest and analyzed using paired sample t-test and N-Gain analysis.The results show an improvement in students’ critical thinking skills after the use of Canva, indicated by a significance value of < 0.05 and an N-Gain score in the moderate to high category.Canva-based learning media is proven to be effective in improving students’ critical thinking skills in science learning.